Arabic Language learning strategies - Sideh, Ibrohem; Mamat, Arifin; Che Haron, Sueraya (The Islamic Cultural Centre & The London Central Mosque, 2016)
Language learning strategies (LLS) play key roles in second/foreign language acquisition in that they promote and facilitate language learning. Research into LLS has been increased and burgeoned significantly in the 1970s with the cognitive revolution. Variables related to the choice of LLS use towards learning English as a second/foreign language (ESL/EFL) have been investigated. Researches have been examining the same issue in learning Arabic as a second/foreign language (ASL/AFL), particularly in the context of Prince of Songkla University (PSU), Pattani campus, Thailand. This study investigates LLS used by PSU students (Pattani campus) reading Arabic. The subjects were 123 undergraduates enrolled in the department of Arabic language at all levels (years 1-4).A Strategy Inventory for Language Learning (SILL)developed by Oxford in 1990 was employed as an instrument for the study. The results revealed that PSU students were familiar with all six LLS categories; namely memory, cognitive, compensation, meta-cognitive, affective, and social strategies, with a medium frequency level use for overall strategies (M = 3.10). Among these six , the most frequently used were meta-cognitive, social, and compensation strategies. The least frequently used were cognitive, affective, and memory strategies.